(3TWQ GdZHs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdMeO ddg hGdKfGA Ydjg heSJMbg aChd eG jLH Ydi GdWHjH Cf jHOC Hg ai eYQag GdYdg s
(3BNQgG (B:s
(3aEf JWGHbJ GdTgGOGJ Hg Ydjg CSJYed hEf NGdaJg fRdJ GdJOHjQ GdCUhGH JeJ GdQSGdg HYhf Gddg JYGdi s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
GALS - (3GdLRA (B1 - (3U (B812 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B119 s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHg QVGQGeHhQ (B(423(3)) s
Keywords: (3GdWHs